أهمية الرياضة المدرسية في إكتشاف المواهب الرياضية بالمؤسسات التربوية مرحلة التعليم المتوسط - يسعد, خذير (Institut d'Éducation Physique et Sportive - Mostaganem 2024/2025, 2025)
يهدف هذا البحث إلى معرفة التحديات التي حالت دون تطبيق برنامج خاص بالرياضة المدرسية في مرحلة التعليم المتوسط من أجل اكتشاف مواهب رياضية و إعطائها أهمية من وجهة نظر الأساتذة. ولأجل ذلك إتبعنا المنهج الوصفي المسحي بالإعتماد على إستبيان موجه لأساتذة التربية البدنية والرياضية بمرحلة التلعيم المتوسط، حيث تمثلت عينة الدراسة في (50) أستاذ تربية بدنية ورياضية من مرحلة التعليم المتوسط لمقاطعة الجهة الغربية بولاية غليزان. وتمثلت أهم نتائج البحث في أن الأساتذة يعانون من صعوبات مرتبطة بتطوير الرياضة المدرسية على مستوى المؤسسات التربوية ، سواء من حيث الجانب المالي، و الوقت الزمني لإجراء هذه الحصة أو عدم ملاءمة بعض الأنشطة للفئة العمرية المستهدفة، أو لظروف المؤسسات التربوية من حيث البيئة والفضاء المتاح. // // // // // This research aims to identify the challenges that have hindered the implementation of a specialized school sports program at the middle school level, with the goal of discovering athletic talents and giving them appropriate importance from the perspective of physical education teachers. To achieve this, we adopted the descriptive survey method, relying on a questionnaire directed at physical education teachers at the middle school level. The study sample consisted of 50 physical education teachers from the middle school stage in the western district of Relizane Province. The most significant findings of the study revealed that teachers face several difficulties related to the development of school sports within educational institutions. These challenges include financial constraints, limited time allocated for sports sessions, the unsuitability of some activities for the targeted age group, and issues related to the school environment and available space.
MEPS-2025-9
Keywords: - الرياضة المدرسية - أستاذ التربية البدنية و الرياضية - اكتشاف المواهب الرياضية // // // School Sports - Physical Education Teacher - Discovering Athletic Talents